Suprarenal fixation of endovascular aortic stent grafts: assessment of medium-term to long-term renal function by analysis of juxtarenal stent morphology. - O'Donnell, M.; Sun, Zhonghua; Winder, J.; Lau, L.; Ellis, P.; Blair, P. (Elsevier, 2007)
Objective: The effect of supra-renal stent fixation during endovascular aortic aneurysm repair (EVAR) on renal function remains unclear. Using a unique validated 3D intraluminal imaging technique, we analysed the effect of suprarenal stent position relative to renal artery orifices and its medium to long term effects on renal function.Methods: Thirty-four consecutive patients from a single institution were studied following EVAR using the Zenith endograft system from September 1999 to March 2002. The precise locations of the uncovered supra-renal stent struts were assessed by a virtual endoscopic imaging technique. Anatomical and quantitative categorisation of patients was made according to the configuration of uncovered stent struts across the renal artery ostia (RAO). The anatomical subgroups were defined as struts located centrally or peripherally across both RAO. The quantitative subgroups were defined as RAO crossed by multiple struts, a solitary strut or no struts. The subgroups were compared for their renal function as assessed by temporal measurements of serum creatinine concentration and creatinine clearance, and renal parenchymal perfusion defects as assessed using contrast-enhanced computerised tomography (CT).Results: Mean follow-up was 52.7 months. Separate subgroup analysis for both anatomical and quantitative configurations did not demonstrate any significant difference in renal function between the different strut permutations (p>0.05). Follow-up imaging confirmed one case of renal infarction secondary to an occluded accessory renal artery, although, this patient had normal creatinine levels.Conclusion: RAO coverage by supra-renal uncovered stents does not appear to have a significant effect on renal function as evaluated by creatinine measurements in patients with normal pre-operative renal function.